HUBUNGAN PENERAPAN METODE TIM DENGAN RENCANA ASUHAN KEPERAWATAN PASIEN DIRUANG RAWAT INAP - Sari ' Madonni; Erwin ' '; Rismadefi ' Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract This study aims to find the correlation between the implementation method of nursing team and nursing care plan in inpatient ward. The study design used  descriptive correlational with cross sectional approach. The study sample is 31 team leaders and 3 patient medical record, team leaders which were choosen using total sampling technique and patient medical records which were choose using simple random sampling technique. The measurement instrument of this study are team method implementation questionnaire and observation sheet for the nursing care plan developed by the researcher and already tested the validity and reability. The analyses used are with univariate analysis with frequency distribution and bivariate with chi square test. The result of team method implementation study showed that team which implement method of team properly have higher number of complete nursing care plan compared to teams that don’t implement method of team properly with a ratio of 12 (38,7%): 3 (6,8%). The result of statistical test with chi square yielded p value = 0,018 > α with α = 0,005 and because of that, it was concluded that there was significant correlation of team method implementation and nursing care plan in inpatient room. This study suggest a proper implementation method of team in a hospital 4 aspect management function to qualified nursing care plan. Keyword: Implementation team method, nursing care plan, team leader